Reintegrasi Sosial Narapidana: Analisis Yuridis Pasca Undang-Undang Pemasyarakatan - Muhammad Farhan; Muhammad Sabir; Kairuddin Kairuddin; Bakhtiar Tijjang; Muh. Akbar Fhad Syahril (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2025)
This study examines the factors that cause the development of inmates outside the Class IIA Correctional Institution (Lapas) of Parepare City and its implementation process. This study uses a qualitative approach with interview methods and document analysis. The results of the study show that coaching outside the prison is based on the need for rehabilitation, reduction of overcapacity, and increasing the social reintegration of prisoners. The coaching process involves three main programs: personality development, independence, and coaching outside the prison, which are carried out in accordance with the Undang-Undang Nomor 22 Tahun 2022 tentang Pemasyarakatan. The implementation of this program reflects a paradigm shift towards a more humane and effective correctional system in preparing prisoners to return to society.